2016
DOI: 10.1088/0964-1726/25/8/084003
|View full text |Cite
|
Sign up to set email alerts
|

The reinforcement and healing of asphalt mastic mixtures by rejuvenator encapsulation in alginate compartmented fibres

Abstract: This paper explores the potential use of compartmented alginate fibres as a new method of incorporating rejuvenators into asphalt pavement mixtures. The compartmented fibres are employed to locally distribute the rejuvenator and to overcome the problems associated with spherical capsules and hollow fibres. The work presents proof of concept of the encapsulation process which involved embedding the fibres into the asphalt mastic mixture and the survival rate of fibres in the asphalt mixture. To prove the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Sodium alginate and PEMA/rejuvenator solutions were then combined in accordance with Tabaković et al [15] with a 70/30 rejuvenator/alginate proportion, found to be optimal for the compartmented alginate fibres. All of the solutions were mixed at 200 rpm for 60 s. It is important to note that the stirring rate and stirring time can be used to control the size of the rejuvenator droplets in the solution and thus the size of the rejuvenator compartments [7,12,16] (The lower the stirring rate and the shorter the stirring time, the larger the droplets; the higher the stirring rate and the longer the stirring time, the smaller the droplets).…”
Section: Compartmented Alginate Fibres Productionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sodium alginate and PEMA/rejuvenator solutions were then combined in accordance with Tabaković et al [15] with a 70/30 rejuvenator/alginate proportion, found to be optimal for the compartmented alginate fibres. All of the solutions were mixed at 200 rpm for 60 s. It is important to note that the stirring rate and stirring time can be used to control the size of the rejuvenator droplets in the solution and thus the size of the rejuvenator compartments [7,12,16] (The lower the stirring rate and the shorter the stirring time, the larger the droplets; the higher the stirring rate and the longer the stirring time, the smaller the droplets).…”
Section: Compartmented Alginate Fibres Productionmentioning
confidence: 99%
“…The emulsions were spun with a plunger-based lab scale wet spinning line in a conventional wet spinning process [12,16,17] to form the rejuvenator-filled compartmented fibres. More details on the fibre preparation and spinning process can be found elsewhere [17].…”
Section: Compartmented Alginate Fibres Productionmentioning
confidence: 99%
See 3 more Smart Citations